2004
DOI: 10.1007/s00535-003-1317-2
|View full text |Cite
|
Sign up to set email alerts
|

The clinical characteristics and outcome of intraabdominal abscess in Crohn?s disease

Abstract: Abscess formation was noted in about 10% of patients with CD, with 46% of abscesses occurring in a diseased bowel segment near an anastomotic site. Of the diseased bowel segments responsible for abscess formation, half had neither severe stenosis nor multiple fistulas. Almost all patients underwent surgery for the abscess, and, in more than a quarter of the patients, there was recurrence within a few years after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(22 citation statements)
references
References 12 publications
0
19
1
2
Order By: Relevance
“…No difference was observed before treatment between patients in the EN and non-EN groups with regard to patient demography, duration of CD, BMI, history of abdominal surgery, co-morbidities, prior medical therapy within three months, characteristics of IAA and laboratory values. About 48.3% of patients in this study underwent a surgical intervention after a median follow-up of 1.9 (1.1-2.9) years, which was lower than the rate of 80% reported in the study by Yamaguchi (1) in 2004. This might be due to the increasing use of interventional procedures such as percutaneous drainage over the past decade (36).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…No difference was observed before treatment between patients in the EN and non-EN groups with regard to patient demography, duration of CD, BMI, history of abdominal surgery, co-morbidities, prior medical therapy within three months, characteristics of IAA and laboratory values. About 48.3% of patients in this study underwent a surgical intervention after a median follow-up of 1.9 (1.1-2.9) years, which was lower than the rate of 80% reported in the study by Yamaguchi (1) in 2004. This might be due to the increasing use of interventional procedures such as percutaneous drainage over the past decade (36).…”
Section: Discussioncontrasting
confidence: 68%
“…Consequently, the occurrence of spontaneous intra-abdominal abscess (IAA) is common in CD patients. Approximately 10% to 30% of patients with CD will spon-taneously develop IAA during the course of the illness (1,2). Management of CD patients with IAA is challenging and requires the expertise of multiple specialists working together.…”
Section: Introductionmentioning
confidence: 99%
“…513 In this study, 23% of patients in the percutaneous drainage group required another intervention, and 15% of patients eventually required surgery. In most cases, surgery was successfully avoided.…”
Section: Discussionmentioning
confidence: 64%
“…1,67,11 The presence of an associated fistula was not evaluated in this study. Yamaguchi et al 10 suggested the importance of prior surgical history in evaluating patients for conservative therapy. In their study, 85% of patients successfully treated conservatively had no prior surgical history compared with 25% of patients who eventually required surgery.…”
Section: Discussionmentioning
confidence: 99%
“…CD is characterized by full-thickness inflammation of the bowel. Therefore, perforating complications such as an intra-abdominal abscess or a fistula, due to transmural translocation of bacteria from the diseased bowel to contiguous tissue, are common and should be regarded as serious complications during the disease course in these patients [1]. In the literature, occurrence rates for intra-abdominal abscesses vary from 10 to 30% [1].…”
Section: Introductionmentioning
confidence: 99%